Supplementation of egg white peptides on attenuating skin mechanical damage symptoms: a promising way to accelerate wound healing process. Issue 17 (20th July 2021) - Ge, Huifang; Jiang, Yiqun; Ning, Zhenzhen; Hu, Zhiqing; Ma, Sitong; Shao, Yin; Liu, Jingbo; Zhang, Ting
Abstract : EWPs have high antioxidant activity without toxicity, which can also promote HSF cell migration in a dose-dependent manner. Moreover, EWPs can accelerate wound healing process by supplementing amino acids and inhibiting oxidative stress. Abstract : Recent studies have indicated that active peptides can induce an improvement in wound repair. Herein, we evaluated egg white peptides (EWPs) as a nutritional supplement to improve mechanical skin damage in BALB/c mice. Two symmetrical circular full-thickness wounds were created with 5 mm biopsy punches in the skin of the mouse dorsal region, and EWPs (200, and 400 mg kg −1 ) were administrated by gavage for 14 days. We analyzed the EWPs for their in vivo and in vitro antioxidant capability, toxicity, and microscopy of skin wounds, and there was no cytotoxicity or in vivo toxicity. During the period of wound healing, EWPs could promote healthy cell migration, increase serum superoxide dismutase and catalase activities and accelerate the wound healing process in a time- and dose-dependent manner, whereas the levels of malondialdehyde and reactive oxygen species showed the opposite trend. After administration with 400 mg kg −1 EWPs for 10 days, the wound had almost healed. Meanwhile, EWPs significantly enhanced serum amino acids, particularly enhancing the content of Arg, Glu, Pro, Met, and Lys, which could provide sufficient nutrition in the wound healing process. The present study demonstrates that EWPs possess a positive potential to accelerate the wound healing process of mechanical skin damage at the cellular and animal level.